2023
DOI: 10.21303/2461-4262.2023.002509
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of acoustic emission and vibration signals in monitoring tool wear, surface quality and chip formation when turning SCM440 steel using MQL

Abstract: With modern production, Minimum Quantity Lubricant (MQL) technology has emerged as an alternative to conventional liquid cooling. The MQLs is an environmentally friendly lubricant method with low cost while meeting the requirements of machining conditions. In this study, the experimental and analytical results show that the obtained acoustic emission (AE) and vibration signal components can effectively monitor various circumstances in the SCM440 steel turning process with MQL, such as surface quality and chip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Current had a low contribution to predictions in their experiments. Similarly, the results reported by Hoang et al [18] indicated the ability of AE and vibrations to predict wear and roughness in the machining of SCM440 steel, combining a Gaussian process regression and adaptive neuro-fuzzy inference system (GPR-ANFIS) algorithms to process RMS values of the signals, achieving an average prediction accuracy of 97.57% in online monitoring with the proposed methodology.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…Current had a low contribution to predictions in their experiments. Similarly, the results reported by Hoang et al [18] indicated the ability of AE and vibrations to predict wear and roughness in the machining of SCM440 steel, combining a Gaussian process regression and adaptive neuro-fuzzy inference system (GPR-ANFIS) algorithms to process RMS values of the signals, achieving an average prediction accuracy of 97.57% in online monitoring with the proposed methodology.…”
Section: Introductionsupporting
confidence: 66%
“…Several literature reviews have identified the main techniques, tools and trends for processing [21][22][23][24]. Firstly, signals are processed directly in the time domain [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] or techniques or transforms are used for their analyses in the frequency [3,5,[18][19][20] or time-frequency [19,20] domains. From here, several techniques are used to obtain features that allow the analysis to be carried out in a better way, such as the use of statistical indicators [3][4][5][6]8,14,[18][19][20], time or time-frequency transforms for direct feature extraction [3][4][5]19,20] and, in some cases, methods for the selection of the most appropriate features or dimensionality reduction such as heuristic techniques [5,6,22], linear discriminant analysis (LDA) [19] or principal component analysis (PCA).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations